SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PESERTA LELANG TENDER PEMERINTAH MENERAPKAN PROMETHEE II - Mesran Mesran; Suginam Suginam; Suci Hildayani (LPPM Politeknik LP3I Medan, 2019)
A tender auction is a series of processes from bidding made by the contractor to the decision of the contractor selected as the winner of the tender. The selected contractor will carry out the work in the field in accordance with the rules and procedures issued by the government. The submission process to be a more selective list of bidders makes the government use a decision support system that can provide effective information to the selected tender participants so that the decisions that the government produces are better and more objective. The application of the Promethee II method in supporting the feasibility decision of tender participants is very optimal because each alternative will be compared with each other so that the results obtained from the comparison are the best.